Primary breakup of power-law biofuel sprays in pressurized gaseous crossflow. (15th December 2019) - Jiao, Daokuan; Jiao, Kui; Zhang, Fan; Bai, Fuqiang; Du, Qing
Highlights: The near nozzle field characteristics of power-law behavior biofuel sprays are investigated. The effects of momentum flux ratios, Weber number and density ratios are discussed. Power-law behavior biofuel shows great advantages in bringing a better atomization. Column deflection, furcation, penetration core length and break points are identified. Instability growth on the column surface have been detected and analyzed. Abstract: The spray characteristics of biofuels have attracted broad interests, due to its bright prospect as one of the alternative fuels. The rheology of some biofuels was found to be power-law behavior. The spray performance of these fuels still remains unclear. Besides, biofuel atomization in pressurized gaseous crossflow can be of interest for combustion engines. The influential factors, namely the momentum flux ratios, Weber number and liquid-gas density ratios, are investigated employing controlling variable approach in the present. Power-law behavior fuel has shown great advantages in bringing a better atomization compared to the Newtonian one with case-control method. Jet column surface disturbance and the deformation magnitude during the injection process is emphasized. The penetration core lengths and breakup points are identified to illustrate the column deformation and breakup times. Besides, the column furcation processes which form finger-like features, as well as surface wavelengths are detected and compared along the studies of the influential factors. A larger injection momentum brings a smaller column deflection while the deflection is independent of Weber number. Besides, the locations of the furcation points increase with the raise of the momentum flux ratios while reduce with the increase of Weber number. The significant effect for increasing the density ratios is on promoting jet atomization. Column breakup processes tend to take place when keep increasing the gas densities. The column surface fluctuations are enhanced while the quantity of the ligaments raises and the shapes become richer.